Origin, genetic diversity, adaptive evolution and transmission dynamics of Getah virus. Issue 4 (13th December 2021) - Shi, Ning; Zhu, Xiangyu; Qiu, Xiangshu; Cao, Xinyu; Jiang, Zhenyan; Lu, Huijun; Jin, Ningyi
Abstract: As a member of the Alphavirus, Getah virus (GETV) was becoming more serious and posing a serious threat to animal safety and public health. However, the circulation, distribution and evolution of GETV is not well understood. Hence, we integrated a variety of bioinformatic methodologies, from genomic alterations to systematic analysis, phylogeography, selection, adaptive analysis, prediction of protein modification, structural biology and molecular dynamics simulations to understand the characteristics of GETV. The results of phylogeography and molecular evolution show that due to the lack of vaccine, GETV is rapidly expanding its host range and geographical distribution at a high evolutionary rate. We also predicted the important modification sites, and identified the adaptive and active selection sites. Finally, the analysis of spatial structure and function showed that six adaptive sites may be related to the structural stability, receptor binding ability, immunogenicity and immune evasion of the virus, respectively. The data from this study have important implications for the understanding of ongoing GETV outbreaks worldwide and will guide future efforts to develop effective preventive and control measures against GETV. In particular, biosafety measures should be strengthened immediately to prevent GETV from becoming a pandemic, especially in China, South Korea and Japan.